Teachers' Beliefs about Language Teaching and Learning: Implications for Teaching Unplugged - Nureldeen, Waleed (JET (Journal of English Teaching), 2020)
The role of teaching materials in ELT has usually been a controversial issue in terms of what type of materials teachers should use and how important these materials are to language teaching and learning. This controversy got heated by the advent of calls for material-light classrooms and using teachers and learners as resources to liberate ELT from the ‘tyranny’ of course books. Nevertheless, these calls remain to carry a relatively little weight in mainstream ESL/EFL teacher education circles. They are communicated to teachers and educators, mainly through professional development arenas. Since we know very little about what attitudes teachers hold to these calls, we cannot assess their magnitude and influence. This article investigates Egyptian EFL teachers' beliefs pertaining to the tenets of Dogme (i.e., an approach that advocates material-free English language teaching) in relation to teachers' gender, years of experience, and the age group they teach, intending to explore the variable(s) that may influence beliefs about Dogme. Data were collected from 70 Egyptian EFL teachers using a questionnaire. Quantitative analysis of data revealed that generally, there is no significant relationship between teachers' beliefs about Dogme and the variables mentioned above.